Indications for 3-D diagnostics and navigation in dental implantology with the focus on radiation exposure: a systematic review - Burkhard Kunzendorf; Hendrik Naujokat; Jörg Wiltfang (SpringerOpen, 2021)
Abstract Background Dental implants are a common restorative method used to replace missing teeth. Implant placement techniques guided by three-dimensional imaging and navigation are becoming more widely available. Objective The present review focused on the following questions: 1. What are the advantages and disadvantages of 2-D versus 3-D imaging in dental implantology? 2. What are the advantages and disadvantages of freehand implant placement in comparison with navigation-guided implant placement? Methods A systematic review was performed, based on the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statement. The following libraries were searched for relevant literature: PubMed, Embase, Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften (AWMF) Online, and the Cochrane Library. The risk of bias was assessed using the Scottish Intercollegiate Guidelines Network (SiGN) checklist. A total of 70 studies were included after screening, and the evidence from these was gathered for review. Results Three-dimensional imaging is advantageous in terms of image quality, and it provides a distortion-free evaluation of the implant site. However, it is also associated with higher costs and increased radiation exposure. Dynamic and static navigation are equal in accuracy and are both more accurate compared with the freehand method. No benefit in terms of implant survival could be demonstrated within the first 5 years for any specific method. Discussion A panoramic X-ray with a reference body often provides sufficient imaging and is the primary method for two-dimensional imaging. Cone beam computed tomography with low-dose protocol settings should be used if three-dimensional imaging is needed. Navigational support should be considered in the event of especially complex cases. Conclusion The guidance technique used for implant placement should be decided on an individual basis. With the increasing availability of three-dimensional imaging, there should also be an increase in awareness of radiation exposure.